Partisipasi Suami dalam Penggunaan Vasektomi di Kota Kupang - Rahmawati Alil; Tadeus A. L. Regaletha; Enjelita M. Ndoen (Universitas Nusa Cendana, 2020)
Vasectomy is a contraceptive method for men or families who no longer want children. This method has a success rate of 99.8% and is very safe to use. Nevertheless, the number of men’s participation in the family planning program (KB), especially vasectomy, in Kupang was significantly low. Only 78 of 893 men who participated in KB were vasectomy acceptors. This fact was different from the number of participants for tubectomy in the city, which reached 2.687 acceptors in 2019. Practically, surgery for tubectomy is more complicated than vasectomy surgery. This study aimed to explore the reasons some husbands decided to participate in vasectomy. This research was a qualitative study with five informants. The results showed that the informants had both good understanding and positive attitude towards vasectomy. Also, the informants obtained socio-cultural support, easy access to the place of health services, and their spouses’ support in vasectomy participation. Socialization on vasectomy should address benefits, side effects, and other factors causing vasectomy to be considered taboo by the public. This will help change people’s incorrect mindset about vasectomy and increase the number of vasectomy participation. Keywords: Vasectomy, Husband, Participation, Support, Access